Room temperature high hydrogen gas response in Pd/TiO2/Si/Al capacitive sensor - Ratan S.; Kumar C.; Kumar A.; Jarwal D.K.; Mishra A.K.; Upadhyay R.K.; Singh A.P.; Jit S. (My University, 2025)
This Letter reports the high gas response for hydrogen gas (H2) in Pd/TiO2/Si/Al based metal-oxide semiconductor (MOS) sensor. Titanium oxide (TiO2) thin film deposited on the p-type silicon (Si) substrate is used as the gate oxide of the MOS sensor. The surface morphology of thermally evaporated TiO2 thin film is investigated for the film structure using atomic force microscopy and scanning electron microscopy. The proposed MOS sensor characterised by capacitance-voltage (C-V) and conductance-voltage (G-V) measurements under exposure of different concentration of H2 gas at room temperature in the ambient-air atmosphere. The maximum gas response of 65% calculated from the change in capacitance and 84% calculated from the change in conductance are obtained for the exposure of 4% of H2 gas. The obtained maximum gas responses are highly promising for low concentration detection of hydrogen gas (4%) using the fabricated MOS sensor operated at room temperature under zero bias voltage condition. © The Institution of Engineering and Technology 2020.